PERAN MINDFULNESS DALAM KEMAMPUAN BERPIKIR KRITIS MATEMATIKA SISWA SEKOLAH DASAR: SYSTEMATIC LITERATURE REVIEW - Reno Ardi Pranoto; Laelia Nurpratiwiningsih; Farhan Saefudin Wahid (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the role of mindfulness in improving mathematical critical thinking skills of elementary school students through the Systematic Literature Review (SLR) method. The study used the PRISMA protocol with data sources obtained from Google Scholar through the Publish or Perish application using the keywords “mindfulness” and “critical thinking.” From 862 articles identified, 15 articles that met the research criteria were selected for analysis. The results showed that critical thinking skills can be improved through various innovative learning approaches such as Problem Based Learning (PBL), STEM, HOTS, interactive multimedia, and strengthening digital literacy. In addition, mindfulness plays an important role in improving students’ focus, concentration, self-awareness, and emotional regulation, thereby supporting critical thinking processes in mathematics learning. Therefore, mindfulness can be an effective approach to support more active and meaningful mathematics learning for elementary school students.